Immunotherapy in head and neck cancer: Harnessing profit on a system disruption. (November 2016) - Rancoule, Chloé; Vallard, Alexis; Espenel, Sophie; Guy, Jean-Baptiste; Xia, Yaoxiong; El Meddeb Hamrouni, Anis; Rodriguez-Lafrasse, Claire; Chargari, Cyrus; Deutsch, Eric; Magné, Nicolas
Highlights: Immunotherapy in SCCHN is based on strong rational targeting intrinsic deregulations. Cetuximab is for now the only monoclonal antibody approved for SCCHN management. Immunotherapies' clinical trials are multiplying in recurrent/metastatic SCCHN. Immune checkpoints openers in SCCHN are arousing enthusiasm. Combination of immunotherapy with current treatments may provide synergistic benefit. Abstract: Immune system deregulation and evasion play a key role in cancers' evolution and progression, including squamous cell carcinoma of the head and neck (SCCHN). Development of basic research proposed a whole new vision of cancer treatment, based on a strong biological rational, and targeting intrinsic deregulations. Immunotherapies provide an encouraging strategy for patients' improved outcomes. Immune-based therapies could act on cancer growth and/or development throughout many pathways. If cetuximab is for now the only monoclonal antibody approved for SCCHN management, other strategies, e.g. immune checkpoints openers, are arousing enthusiasm. Clinical trials are multiplying in patients with recurrent/metastatic SCCHN and primary results offer promising outcomes. Prospects of combining various immunotherapies with more established treatments, such as chemotherapy and radiotherapy, seem very encouraging and could provide synergistic benefits. Ongoing phase III clinical trials should soon enlighten us on the next "standard of care" for SCCHN. In the present review we summarized the different immunotherapy strategies that are currently under clinical investigation for SCCHN' medical care.